Peran Moderasi Sumber Daya Kerja pada Hubungan Antara Stres Digital dengan Burnout - Puspita, Debora Dwi; Zamralita (Psyche 165 Journal, 2023)
During the Covid-19 pandemic, the work system changed to work from home. The existence of a new system has an impact on the way the work system. One of the impacts of work from home is excessive use of technology of work. Excessive use of technology has an impact on employees such as digital stress and over work. Digital stress experienced by employees can cause fatigue both physically and psychologically. Emotional exhaustion experienced by employees can cause burnout. There are three variables in this study, namely digital stress, burnout, and job resources. This study aims to see the effect of digital stress burnout on the moderation of job resources. This research uses quantitative methods, there are 102 participants in this research. This research uses convenience sampling. The measuring tools of this research are the digital stress scale, burnout assessment tools, and the job demands–resources questionnaire. The result of this study is that the level of digital stress (M=2,89) and burnout (M=2,10) are classified as low, and the level of job resources (M=4,03) is high. It was found that there is a significant correlation between digital stress with burnout, job resource with digital stress and burnout with job resources. Digital stress has correlation with burnout (r=0,509), digital stress has correlation with job resources (r=-0,265) and job resources has correlation with burnout (r=-0,388). In this study, job resources can't moderate digital stress to burnout.